2014
DOI: 10.1001/jamaoto.2013.5988
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life Among Long-Term Survivors of Head and Neck Cancer Treated by Intensity-Modulated Radiotherapy

Abstract: Our findings add to the body of literature that supports the acceptance of IMRT as standard treatment for head and neck cancer. The fact that most 5-year survivors were satisfied with their quality of lives points to the ability of IMRT to preserve long-term functioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 20 publications
2
47
0
7
Order By: Relevance
“…The mean 15D score in this study was in the same range as shown in patients with colorectal [20] and prostate cancer [21]. Previous studies on oncologically treated head and neck cancer patients show that a decline in HRQoL is usually seen during the first 3 months after treatment onset, but it then gradually improves towards 12 months [8,22] and even 5 years after treatment patients are satisfied with their QoL [23]. This trend of improvement was also obvious in our study.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The mean 15D score in this study was in the same range as shown in patients with colorectal [20] and prostate cancer [21]. Previous studies on oncologically treated head and neck cancer patients show that a decline in HRQoL is usually seen during the first 3 months after treatment onset, but it then gradually improves towards 12 months [8,22] and even 5 years after treatment patients are satisfied with their QoL [23]. This trend of improvement was also obvious in our study.…”
Section: Discussionsupporting
confidence: 86%
“…Dependence of gastrostomy tube (PEG) during oncological treatment for oropharyngeal carcinoma is 81 % [26], but longer periods are uncommon [23]. This will positively affect QoL during the later recovery [24].…”
Section: Discussionmentioning
confidence: 99%
“…The curative treatment of HNSCC involves radiotherapy in a multimodality approach, which is accompanied by adverse effects resulting from damage to healthy tissue surrounding the treated area . The resulting short‐ and long‐term side effects of radiation therapy include mucositis, pain, and xerostomia, which significantly compromise the patient's quality of life . Minimizing these side effects can be achieved by enhanced tissue regeneration of the affected area, which is largely dependent on the survival and regenerative abilities of tissue‐resident or invading stem cells .…”
Section: Discussionmentioning
confidence: 99%
“…Omission of retropharyngeal and high level II nodal stations in OPC patients has been shown to improve dysphagia outcomes [23], as well as minimize parotid dose [24]. While sparing of level V may not result in the same impact as sparing upper neck nodal basins, potential benefits include lower risks of dermatitis, brachial plexopathy [25], neck fibrosis and spasm [26], and shoulder dysfunction [27], particularly as the spinal accessory nerve runs superficially through level V and surgical manipulation can result in significant shoulder impairment [28, 29]. Because most of these events are late toxicities, detection of a difference with LVN omission would require both large sample sizes and extended follow-up.…”
Section: Discussionmentioning
confidence: 99%